Ionization of the Polar Atmosphere by Energetic Electron Precipitation Retrieved From Balloon Measurements. Issue 2 (16th January 2019) - Mironova, I. A.; Artamonov, A. A.; Bazilevskaya, G. A.; Rozanov, E. V.; Kovaltsov, G. A.; Makhmutov, V. S.; Mishev, A. L.; Karagodin, A. V.
Abstract: We retrieve ionization rates in the atmosphere caused by energetic electron precipitation from balloon observations in the polar atmosphere and compare them against ionization rates recommended for the Phase 6 of the Coupled Model Intercomparison Project. In our retrieval procedure, we consider the precipitating electrons with energies from about tens of keV to 5 MeV. Our simulations with 1‐D radiative‐convective model with interactive neutral and ion chemistry show that the difference of the Phase 6 of the Coupled Model Intercomparison Project and balloon‐based ionization rate can lead to underestimation of the N O x enhancement by more than 100% and ozone loss up to 25% in the mesosphere. The atmospheric response is different below 50 km due to considering highly energetic electrons, but it is not important because the absolute values of atmospheric impact is tiny. Ionization rates obtained from the balloon observations reveal a high variability. Plain Language Summary: The main idea of our manuscript is to demonstrate that the atmospheric ionization rates (IR) can be successfully retrieved from the long‐term balloon observations of the energetic electron precipitation (EEP) events and used to evaluate the uncertainties of the other IR data sets, for example, IR recommended for the Phase 6 of the Coupled Model Intercomparison Project (CMIP6). IR obtained from the balloon observations reveal a high variability. This means that the time resolution used in CMIP6 probably is not enough to consider high frequency variability of the precipitating electron fluxes. Using 1‐D radiative‐convective model with neutral and ion chemistry, we compared the atmospheric response to the one particular EEP observed by balloons and presented in CMIP6 data. We show that the difference of the CMIP6 and balloon‐based IRs can lead to underestimation of the NO x enhancement by more than 100% and ozone loss by up to 25% in the mesosphere. Our results are new and needed for the understanding of the potential uncertainties in CMIP6 EEP forcing. Our paper will give inspiration for the continuation of the balloon measurements of EEP‐related processes using improved instruments. Key Points: Ionization rates (IR) from energetic electron precipitation (EEP) are calculated using balloon observations and compared to the CMIP6 data set The difference in the atmospheric response calculated with these two data sets can exceed 100% for N O x and reach 25% for O 3 IR obtained from balloon measurements reveal a high temporal variability, which is absent in CMIP6 data